Pengaruh Tekanan dan Jenis Bahan Bakar Terhadap Konsumsi Bahan Bakar Spesifik - Muhamad Fatikhun Nada; Santoso Santoso (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The three main factors determining combustion efficiency in Otto engines are optimal compression pressure, effective ignition, and fuel quality. In this study, two critical variables—fuel pump pressure (38, 43, and 48 Psi) and fuel type (RON 90 and RON 92)—were analyzed to understand their impact on specific fuel consumption (SFC). An experimental research method was employed to test the effect of independent variables on dependent variables under controlled conditions. The results indicate that a fuel pump pressure of 43 Psi provides the most stable and efficient fuel consumption performance for both fuel types across the entire engine speed range. A fuel pump pressure of 38 Psi is optimal at medium engine speeds but less efficient at high speeds, whereas a pressure of 48 Psi is most efficient at low to medium speeds but decreases in efficiency at high speeds. Overall, RON 92 fuel shows an efficiency improvement over RON 90, particularly at medium to high engine speeds. The combination of a fuel pump pressure of 43 Psi and the use of RON 92 fuel is recommended to achieve optimal specific fuel consumption, as it provides consistent efficiency across various engine operating conditions.